Organizational culture and its motivational effect on the workers of a private company - Pérez-Pérez, Milagros Judith; Castro-Mejía, Percy Junior; Oyola-Fernández , Maximiliano; Peña-Rivera , María del Carmen; Ruiz-Guerrero , Marli (AiBi Journal of Research, Administration and Engineering, 2024)
The objective of the research was to analyze the organizational culture and its motivational effect on the workers of a private company. The study had a quantitative approach and was of the applied type, with a non-experimental, cross-sectional and correlational design. The population consisted of 100 individuals and a simple random probabilistic sampling was carried out, where the universe of study had the same probabilities of being selected, resulting in the application of the instrument of 80 workers from the private company. For data collection, the technique called survey was used, its instrument being the questionnaire with 36 questions based on the study variables and 5 response options for each one according to a Likert-type scale, which were answered online by the collaborators. The results reflect a significant correlation between the organizational culture and the motivational effect of the workers, with a Spearman correlation coefficient of 0.504** and a p-value of 0.000. This indicated that the organizational culture has a revealing influence on the motivation of the workers of the private company.
Keywords: work motivation; organizational culture; job satisfaction; workers; company